2019
DOI: 10.1107/s1600576719002450
|View full text |Cite
|
Sign up to set email alerts
|

Martini bead form factors for nucleic acids and their application in the refinement of protein–nucleic acid complexes against SAXS data

Abstract: The use of small-angle X-ray scattering (SAXS) in combination with molecular dynamics simulation is hampered by its heavy computational cost. The calculation of SAXS from atomic structures can be speeded up by using a coarse-grain representation of the structure. Following the work of Niebling, Bjö rling & Westenhoff [J. Appl. Cryst. (2014), 47, 1190-1198], the Martini bead form factors for nucleic acids have been derived and then implemented, together with those previously determined for proteins, in the publ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…We conducted SAXS-restrained MD simulation using the metainference metadynamics (M&M) method, where we employed the parallel-bias (PBMetaD) flavour of well-tempered metadynamics (Pfaendtner and Bonomi, 2015) in combination with the multiple-walkers scheme (Raiteri et al, 2006). During the M&M simulation, the SAXS back-calculation step utilises a hybrid-resolution approach, where the SAXS data is calculated on-the-fly using 'Martini beads' that are superimposed on the all-atom structures using PLUMED (Bonomi and Camilloni, 2017;Paissoni et al, 2019Paissoni et al, , 2020Jussupow et al, 2020). The approach is particularly efficient as the SAXS back-calculation is calculated using the Debye equation from a coarse-grained model and the excess of electron density in the hydration shell is neglected (Niebling et al, 2014;Paissoni et al, 2020).…”
Section: Metainference Metadynamicsmentioning
confidence: 99%
“…We conducted SAXS-restrained MD simulation using the metainference metadynamics (M&M) method, where we employed the parallel-bias (PBMetaD) flavour of well-tempered metadynamics (Pfaendtner and Bonomi, 2015) in combination with the multiple-walkers scheme (Raiteri et al, 2006). During the M&M simulation, the SAXS back-calculation step utilises a hybrid-resolution approach, where the SAXS data is calculated on-the-fly using 'Martini beads' that are superimposed on the all-atom structures using PLUMED (Bonomi and Camilloni, 2017;Paissoni et al, 2019Paissoni et al, , 2020Jussupow et al, 2020). The approach is particularly efficient as the SAXS back-calculation is calculated using the Debye equation from a coarse-grained model and the excess of electron density in the hydration shell is neglected (Niebling et al, 2014;Paissoni et al, 2020).…”
Section: Metainference Metadynamicsmentioning
confidence: 99%
“…Despite this difference in sampling, both approaches perform rather similarly in terms of structure quality, indicating that our CG protocol is also applicable for integrative modeling of complexes in combination with real experimental data. Recent studies have indicated that the interpretation of CG models using experimental data, and in particular SAXS data, can benefit from improved forward models as demonstrated by Paissoni et al (2019) for protein-DNA complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, SAXS intensities were also explored as a source of experimental information to be used with metainference. Paissoni and coworkers exploited this strategy to investigate the conformational ensemble of K63-linked diubiquitin [148] and to refine models of nucleic acid-protein complexes [149]. Similarly, Kooshapur et al used SAXS experimental data in a metainference framework to derive a structural model of a complex between an RNA-binding protein and a microRNA [150].…”
Section: Enforcing Experimental Information During the Simulationsmentioning
confidence: 99%